2019
DOI: 10.3390/nu11071497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Processing towards Lower Rapidly Available Glucose (RAG) Favors Idli, a South Indian Fermented Food Suitable for Diabetic Patients

Abstract: The Asian food pattern primarily embraces rice and rice-based products, which mainly comprise 90% starch. Among these various food products, Idli is mostly prepared through fermentation. It has high palatability, and the rapid and highly digestible nature of the food product results in a higher post-glucose level in diabetic patients. A heat-treated Idli rice sample was prepared by roasting parboiled rice at the temperature range of 155 to 165 °C for 65 to 75 s. Idli/rice-based Dokala made from heat-treated ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Rice is known for its anti-oxidant and chemoreceptive properties, and the red colour of this rice is due to the presence of pigment "proanthocyanidin" (Mehra et al, 2020) [18] .When cooked rice is left overnight the bacteria growth enhances and lactic acid produces during fermentation and result in enhancing of vital macronutrients, minerals like iron phosphorous. Rice due to its high glycaemic index 85 can cause diabetes to the consumer that is why it is advised to eat rice with something like curry that ultimately lowers its glycaemic index and also in research it is found that protein quality found in rice is much better than whey and soy protein (Chelliah et al, 2019;Phongthai et al, 2017) [19,20] . Parboiled rice is also good source of nutrients and it is lower down the glycemic index and ultimately it is beneficial for type-2 diabetics person.…”
Section: Rice (Oryza Sativa)mentioning
confidence: 99%
“…Rice is known for its anti-oxidant and chemoreceptive properties, and the red colour of this rice is due to the presence of pigment "proanthocyanidin" (Mehra et al, 2020) [18] .When cooked rice is left overnight the bacteria growth enhances and lactic acid produces during fermentation and result in enhancing of vital macronutrients, minerals like iron phosphorous. Rice due to its high glycaemic index 85 can cause diabetes to the consumer that is why it is advised to eat rice with something like curry that ultimately lowers its glycaemic index and also in research it is found that protein quality found in rice is much better than whey and soy protein (Chelliah et al, 2019;Phongthai et al, 2017) [19,20] . Parboiled rice is also good source of nutrients and it is lower down the glycemic index and ultimately it is beneficial for type-2 diabetics person.…”
Section: Rice (Oryza Sativa)mentioning
confidence: 99%
“…A study showed Idli/rice-based Dokala made from heat-treated rice is better when compared to untreated rice in terms of its microbiological profile and physiochemical properties. The proximate composition of heat-treated parboiled rice Idli/Rice Dokala showed slightly higher values than the untreated parboiled rice Idli/Rice Dokala, which reveals that it has marginally higher nutritive value (Chelliah, 2019). Bamboo shoot is another food item which has been used by various tribes as well as in specific regions of India since ages.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies on nutritional aspect of Idli determined the Rapidly Available Glucose (RAG) and Slowly Available Glucose (SAG) values, SEM analysis, resistant starch analysis, microbial assay, and in vivo study analysis were performed to determine the glycemic index (GI) and glycemic load in normal and diabetic persons. Sensory analysis also proved that heat-treated Idli/Rice Dokala is superior to untreated ones based on their color, flavour, appearance, taste, and texture (Chelliah et al, 2019). Another study compared observations of the first and the fifth day samples of idli batter and showed variations in the nutrient content.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is grown in many Asian countries and is consumed as a staple grain in human diets. Many studies have examined the starch properties of rice that are related to the variety or processing method ( Arns et al, 2015 ; Chelliah et al, 2019 ; Kim et al, 2021a ); polished white rice contains more than 75% starch and has low fiber content ( Li et al, 2004 ). Paddy rice is processed in several steps to produce polished final products such as brown and white rice for human consumption ( Kaur et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%